2013
DOI: 10.1525/jer.2013.8.1.68
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Participatory Research Study of HIV and HPV Vulnerabilities and Prevention in Two Pacific Islander Communities: Ethical Challenges and Solutions

Abstract: We describe ethical issues that emerged during a one-year CBPR study of HIV and human papillomavirus (HPV) vulnerabilities and prevention in two Pacific Islander (PI) communities, and the collaborative solutions to these challenges reached by academic and community partners. In our project case study analysis, we found that ethical tensions were linked mainly to issues of mutual trust and credibility in PI communities; cultural taboos associated with the nexus of religiosity and traditional PI culture; fears o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Analysis of the methodologies of the selected papers indicated that most of the researchers (ten out of fourteen) adopted a qualitative approach (Dela Cruz et al, 2016;Devries et al, 2010;DiStefano et al, 2012;2013;Henderson et al, 2018;Hodge, 2014;Itty et al, 2014;Nonzee et al, 2018;Soon et al, 2015); three were based on quantitative analysis (Dwojak et al, 2015;Gabster et al, 2019;Tom et al, 2016); and one had a mixed-methods approach (Hodge et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the methodologies of the selected papers indicated that most of the researchers (ten out of fourteen) adopted a qualitative approach (Dela Cruz et al, 2016;Devries et al, 2010;DiStefano et al, 2012;2013;Henderson et al, 2018;Hodge, 2014;Itty et al, 2014;Nonzee et al, 2018;Soon et al, 2015); three were based on quantitative analysis (Dwojak et al, 2015;Gabster et al, 2019;Tom et al, 2016); and one had a mixed-methods approach (Hodge et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, conducting CBPR requires building the capacity of both community stakeholders and academic researchers (Crosby et al 2013;Goytia et al 2013;Kwon et al 2012). Though several CBPR engagement and training models have been published (Allen et al 2013;Baquet et al 2013;Cole et al 2013;Crosby et al 2013;Goytia et al 2013;Healey, Reed & Huber 2013;Martin del Campo et al 2013;Rideout et al 2013;Smith, Kaufman & Dearlove 2013;Young-Lorion et al 2013), few have focused on work with Pacific Islander communities (DiStefano et al 2013;Kaholokula et al 2014;Kwan et al 2012Kwan et al , 2014Palmer 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of culturally congruent HIV interventions, the absence of an equivalent comparison group (without a cultural component), as well as the absence of evaluation of the effect of racial pride on behavioral outcomes can obscure the specific importance of culture in HIV prevention among African-American MSM and MSMW (Maulsby et al, 2013; Williams et al, 2009). Findings by DiStefano et al (2013) suggests that racial pride is protective against HIV risk behaviors among Pacific Islander communities, but this association has yet to be quantitatively demonstrated among African-Americans. Therefore, the objective of our study is to assess the pathways by which racial pride is associated with condom use self-efficacy, intentions, and behaviors among post-incarcerated African-American MSMW using baseline data from our intervention, Men in Life Environments ( MILE ) (Harawa et al, 2016).…”
Section: Culture In Hiv Interventionmentioning
confidence: 99%